Monitoring Risso's Dolphins in the Northeast Atlantic: A Deep Learning Approach to Classify Echolocation Click Detections - Thomas Webber; Denise Risch; Gordon Hastie; Rona Sinclair; Suzanne Beck; Per Berggren; Oliver Boisseau; Katie Dyke; Lauren Hartny‐Mills; Claire Lacey; Susanna Quer; Matt Sharpe; et al. (Marine Mammal Science, 2026)
Large volumes of passive acoustic data are collected by researchers, governments, and conservationists across the globe to monitor species for population assessments and conservation objectives. An analysis bottleneck often exists due to the lack of tools to process large datasets and identify detected signals to the species level. Deep learning has been shown to enable fast and effective detection of species‐specific vocalizations. This study developed a Risso's dolphin ( Grampus griseus ) binary echolocation click classifier using a Long Short‐Term Memory neural network. This classifier was trained and validated on 872 visually verified single species encounters collected during towed hydrophone surveys, primarily in the Northeast Atlantic. The classifier was subsequently tested on an independent set of 31 h of visually verified data collected from static and drifting recorders in Scottish and English waters, comprising four different delphinid species (including Risso's dolphins) as well as various sources of anthropogenic noise. The best classifier achieved an F1 score of 0.98 (precision 0.96, recall 0.98). While care must be taken when applying deep learning classifiers to new datasets, the performance of this model on independent data highlights its ability to generalize well within the study region, even when using data collected on different recording platforms.

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Cetaceans and threats of the Ninety East Ridge and high seas of the Indian Ocean - Thomas Webber; Oliver Boisseau; Kirsten F. Young; Francois Provost; Asha de Vos (Marine Environmental Research, 2025)

Threatened cetaceans in a potential deep seabed mining region, Clarion Clipperton Zone, Eastern Pacific, August 2023 - Kirsten F. Young; Thomas Webber; Leonidas Karantzas; Severina Miteva; Grant Oakes; David Santillo; Paul Johnston (Frontiers in Marine Science, 2025)
The Clarion Clipperton Zone (CCZ) of the Eastern Pacific is an ~ 6 million km 2 abyssal area punctuated by seamounts. The CCZ is a focus for potential mining, although this is not, as yet, a commercial reality. Records from online repositories and field guides suggest that up to 30 cetacean species are present in the CCZ, though dedicated surveys have yet to be published. We report the results of a passive acoustic survey for cetaceans conducted over 13 days during summer 2023 in two blocks of the CCZ earmarked for deep seabed mining – NORI-d and TOML-e. The areas surveyed had a mean depth of 4259 m, with no charted seamounts, with 4,328 km of survey effort (273 hours of continuous recordings). In total, there were 74 acoustic detections, with six visual encounters. We report the presence of a sperm whale ( Physeter macrocephalus ) (one individual), Risso’s dolphins ( Grampus griseus ) (two groups) and common dolphins ( Delphinus delphis ) (one group, confirmed by visual sighting). We also acoustically encountered 70 dolphin groups that could not be identified to species level. No baleen whales, kogiids or beaked whales were detected during this short survey. Beaked whales are challenging to detect, such that a lack of detections cannot be taken to confirm the absence of such species. We confirm one threatened species present in these blocks of the CCZ – sperm whales – and suggest that more extensive data are urgently needed to understand the risk of harm to cetaceans that may arise from human activities, including deep-sea mining.

AMPSOM: A measureable pool soil organic carbon and nitrogen model for arable cropping systems - Inès Astrid Tougma; Marijn Van de Broek; Johan Six; Thomas Gaiser; Maire Holz; Isabel Zentgraf; Heidi Webber (Environmental Modelling & Software, 2025)

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Cetaceans of the Saya de Malha bank region, Indian Ocean: A candidate Important Marine Mammal Area - Thomas Webber; Tim Lewis; Sheena Talma; Shaama Sandooyea; Laura Meller; Violaine Dulau-Drouot; Kirsten F. Thompson (Regional Studies in Marine Science, 2023)

Biological soil crusts as a major ecosystem component in sandization areas of the Brazilian Pampa - Carla L. Webber; Ulisses F. Bremer; Ruhollah Taghizadeh-Mehrjardi; Bettina Weber; Aline Rosa; Thomas Scholten; Steffen Seitz (Geoderma Regional, 2023)

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Climate change impacts on European arable crop yields: Sensitivity to assumptions about rotations and residue management - Babacar Faye; Heidi Webber; Thomas Gaiser; Christoph Müller; Yinan Zhang; Tommaso Stella; Catharina Latka; Moritz Reckling; Thomas Heckelei; Katharina Helming; Frank Ewert (European Journal of Agronomy, 2023)

Responses of Salmonella biofilms to oxidizing biocides: Evidence of spatial clustering - Kerry Guest; Thomas Whalley; Jean‐Yves Maillard; Andreas Artemiou; Barbara Szomolay; Mark A. Webber (Environmental Microbiology, 2022)
The spatial organization of biofilm bacterial communities can be influenced by several factors, including growth conditions and challenge with antimicrobials. Differential survival of clusters of cells within biofilms has been observed. In this work, we present a variety of methods to identify, quantify and statistically analyse clusters of live cells from images of two Salmonella strains with differential biofilm forming capacity exposed to three oxidizing biocides. With a support vector machine approach, we showed spatial separation between the two strains, and, using statistical testing and high‐performance computing (HPC), we determined conditions which possess an inherent cluster structure. Our results indicate that there is a relationship between biocide potency and inherent biofilm formation capacity with the tendency to select for spatial clusters of survivors. There was no relationship between positions of clusters of live or dead cells within stressed biofilms. This work identifies an approach to robustly quantify clusters of physiologically distinct cells within biofilms and suggests work to understand how clusters form and survive is needed. Significance statement Control of biofilm growth remains a major challenge and there is considerable uncertainty about how bacteria respond to disinfection within a biofilm and how clustering of cells impacts survival. We have developed a methodological approach to identify and statistically analyse clusters of surviving cells in biofilms after biocide challenge. This approach can be used to understand bacterial behaviour within biofilms under stress and is widely applicable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Early vigour in wheat: Could it lead to more severe terminal drought stress under elevated atmospheric [CO 2 ] and semi‐arid conditions? - Maryse Bourgault; Heidi A. Webber; Karine Chenu; Garry J. O’Leary; Thomas Gaiser; Stefan Siebert; Fernanda Dreccer; Neil Huth; Glenn J. Fitzgerald; Michael Tausz; Frank Ewert (Global Change Biology, 2020)
Early vigour in wheat is a trait that has received attention for its benefits reducing evaporation from the soil surface early in the season. However, with the growth enhancement common to crops grown under elevated atmospheric CO 2 concentrations (e[CO 2 ]), there is a risk that too much early growth might deplete soil water and lead to more severe terminal drought stress in environments where production relies on stored soil water content. If this is the case, the incorporation of such a trait in wheat breeding programmes might have unintended negative consequences in the future, especially in dry years. We used selected data from cultivars with proven expression of high and low early vigour from the Australian Grains Free Air CO 2 Enrichment (AGFACE) facility, and complemented this analysis with simulation results from two crop growth models which differ in the modelling of leaf area development and crop water use. Grain yield responses to e[CO 2 ] were lower in the high early vigour group compared to the low early vigour group, and although these differences were not significant, they were corroborated by simulation model results. However, the simulated lower response with high early vigour lines was not caused by an earlier or greater depletion of soil water under e[CO 2 ] and the mechanisms responsible appear to be related to an earlier saturation of the radiation intercepted. Whether this is the case in the field needs to be further investigated. In addition, there was some evidence that the timing of the drought stress during crop growth influenced the effect of e[CO 2 ] regardless of the early vigour trait. There is a need for FACE investigations of the value of traits for drought adaptation to be conducted under more severe drought conditions and variable timing of drought stress, a risky but necessary endeavour.

Social network characteristics and predicted pathogen transmission in summer colonies of female big brown bats (Eptesicus fuscus) - Quinn M. R. Webber; R. Mark Brigham; Andrew D. Park; Erin H. Gillam; Thomas J. O’Shea; Craig K. R. Willis (Behavioral Ecology and Sociobiology, 2016)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Generation of large droplet aerosols within microbiological containment using a novel flow-focussing technique - Richard J. Thomas; Daniel Webber; William Sellors; Aaron Collinge; Andrew Frost; Anthony J. Stagg; Stephen C. Bailey; Pramukh N. Jayasekera; Rosa R. Taylor; Steve Eley; Richard W. Titball (Aerobiologia, 2009)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)